2009
DOI: 10.1111/j.1439-037x.2008.00347.x
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Grain Filling Rate and Duration in Bread and Durum Wheat, under Heat Stress after Anthesis

Abstract: Bread and durum wheat genotypes were submitted to heat stress during the grain filling period, and relationships between grain weight and accumulated time from anthesis until maturity, using days after anthesis and growing degree days, were described by cubic polynomials. Maximum grain weight and the duration and rate of grain filling were estimated from the fitted curves. It was found that bread and durum wheat exposure to high temperatures significantly decreased grain weight and hastens physiological maturi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

16
161
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 253 publications
(185 citation statements)
references
References 34 publications
16
161
1
Order By: Relevance
“…Our earlier research with wheat showed that HT stress did not have large impact on the rate of grain filling, but it significantly decreased the grain filling duration, leading to smaller individual grain weights (Prasad et al 2008b). High temperature accelerates the rate of grain filling, but shortens grain filling duration (Dias and Lidon 2009). For every 1 C above the optimal growing temperature of 15À20 C, the duration of grain filling was estimated to be reduced by 2.8 days in wheat (Streck 2005).…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations
“…Our earlier research with wheat showed that HT stress did not have large impact on the rate of grain filling, but it significantly decreased the grain filling duration, leading to smaller individual grain weights (Prasad et al 2008b). High temperature accelerates the rate of grain filling, but shortens grain filling duration (Dias and Lidon 2009). For every 1 C above the optimal growing temperature of 15À20 C, the duration of grain filling was estimated to be reduced by 2.8 days in wheat (Streck 2005).…”
Section: Discussionmentioning
confidence: 96%
“…In addition, morphological characters such as stigma hyperplasia and stamen hypoplasia can result in failure of pollination (contact of pollen with stigma) and the fertilisation process (Takeoka et al 1991). Changes in composition and concentrations of carbohydrates (Jain et al 2007), lipids and reactive oxygen species (Djanaguiraman et al 2013a(Djanaguiraman et al , 2013b(Djanaguiraman et al , 2014 in pollen gains result in pollen sterility. Additional research is required to test these principles in wheat.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…), harvest index (HI) and WUE were also statistically high under normal field conditions (T 1 ) than controlled condition's (T 2 ). Heat stress results in severe kernel abortion (Wardlaw and Wrigley, 1994) and its improper maturation (Hays et al, 2007) and higher temperature hindered food translocation because of osmoregulation effect under heat stress (Plaut et al, 2004), reduced grain filling period (Dias and Lidon, 2009), retarding endospermic cells proliferation, so ultimately declined in grain weight (Feng et al, 2000) was reported. Fertile tillers and harvest index under different irrigation levels were statistically significant and gradually decreasing trend was observed as irrigation levels decreased.…”
Section: Discussionmentioning
confidence: 99%